2021
DOI: 10.3390/diagnostics11101928
|View full text |Cite
|
Sign up to set email alerts
|

SERPINE2 Overexpression Is Associated with Poor Prognosis of Urothelial Carcinoma

Abstract: Recent studies have reported that SERPINE2 contributes to the development of various cancers. However, its association with urothelial carcinoma (UC) remains unclear. In this study, data on urinary bladder UC (UBUC) cases from The Cancer Genome Atlas (TCGA) database were used to investigate the prognostic value of SERPINE2 mRNA expression. Then, SERPINE2 expression was analyzed with tissue microarrays constructed from 117 upper tract UC (UTUC) and 84 UBUC tissue specimens using immunohistochemical staining. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
2
7
2
Order By: Relevance
“…They are involved in calcium homeostasis. A novel study conducted by Godinez et al (2022) has revealed that neuroserpin plays an important role in mediating neurite outgrowth and axonal development as well as in maintaining normal synaptic plasticity through its inhibitory effects on the tissue plasminogen activator (tPA) in the CNS, thereby preventing tPA interaction with the NMDA receptor-mediated calcium influx, which contributes to excitotoxic neuronal apoptosis. , The elevated expression of serpin superfamily proteins was associated with low survival and increased recurrence rates …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…They are involved in calcium homeostasis. A novel study conducted by Godinez et al (2022) has revealed that neuroserpin plays an important role in mediating neurite outgrowth and axonal development as well as in maintaining normal synaptic plasticity through its inhibitory effects on the tissue plasminogen activator (tPA) in the CNS, thereby preventing tPA interaction with the NMDA receptor-mediated calcium influx, which contributes to excitotoxic neuronal apoptosis. , The elevated expression of serpin superfamily proteins was associated with low survival and increased recurrence rates …”
Section: Discussioncontrasting
confidence: 99%
“…95,96 The elevated expression of serpin superfamily proteins was associated with low survival and increased recurrence rates. 97 Another identified protein encoded by CAMK (2A, 2B, 2D) is a member of the N-methyl-D-aspartate receptor (NMDAR) signaling complex in excitatory synapses regulating the NMDAR-dependent potentiation of the AMPA receptor and therefore excitatory synaptic transmission. 34 It acts autonomously after ca 2+ /calmodulin binding and autophosphorylation and is involved in synaptic plasticity, neurotransmitter release, and long-term potentiation.…”
Section: Potential Pathways Affected By the Selected Pesticide Mixturecontrasting
confidence: 99%
“…The mouse model of breast tumor heterogeneity demonstrated that SERPINE2 provokes tumor cells to form vascular networks that mimic blood vessels to facilitate tumor cells penetration and metastasis, indicating that SERPINE2 is a dominant driver of metastatic progression [ 30 ]. Simultaneously, high SERPINE2 expression was an independent poor prognostic factor in oral squamous cell carcinoma (OSCC), lung adenocarcinoma, urothelial carcinoma and endometrial cancer [ 31 , 32 , 33 , 34 ], and SERPINE2 was identified as a promising therapeutic target in melanoma metastasis and in the radio-resistance of lung cancer. SERPINE2 promotes radio resistance by mediating the interaction of MRE11 with ATM to induce ATM phosphorylation in homologous recombination (HR)-mediated double strand break (DSB) repair [ 28 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serine protease inhibitor branch E member 2 (SERPINE2), also known as protease ligand protein‐1, is a member of the serine protease inhibitor superfamily. Studies have shown that aberrant expression of SERPINE2 contributes to tumorigenesis and tumor invasion in a variety of cancers, including breast, pancreatic, colorectal, gastric, testicular, cutaneous melanoma, osteosarcoma, thyroid, oral squamous cell, endometrial, esophageal squamous cell, lung, and hepatocellular carcinomas 46–51 . In lung cancer, SERPINE2 is involved in tumor treatment resistance by attenuating DNA damage.…”
Section: Discussionmentioning
confidence: 99%